(untitled) (Journal of Mathematics Mechanics and Computer Science, 2012)
The paper briefly discusses existing models of natural languages’s syntax and describes link grammar in detail. Its general description is given, an example of link grammar application for Kazakh language is described. Implementation of a link grammar parser is described in detail, and a method for automating the process of grammatical file forming is proposed.